Malgacheliodes martensi spec. nov. (Acari, Oribatida, Licnodamaeidae) from South Africa - Ermilov, Sergey G.; Hugo-Coetzee, Elizabeth A.; Khaustov, Alexander A. (Zootaxa, 2021)
The genus Malgacheliodes is recorded in South Africa for the first time. Malgacheliodes martensi spec. nov. is described from soil of Hogsback State Forest, Eastern Cape Province. Adults of the new species differ from those of Malgacheliodes guillaumeti by the presence of ribs and furrows in the aggenital region, bacilliform leg tracheae, rounded ventral keel on leg I femur and four pairs of notogastral setae (h1 absent); while its tritonymph differs from that of M. guillaumeti by the presence of five pairs of gastronotic setae (c1 absent). The generic diagnosis of Malgacheliodes is updated. The differences in morphology of the tritonymphal instar in Malgacheliodes and other genera of Licnodamaeidae are presented.